HUKUM TINDAK PIDANA MAYANTARA (CYBER CRIME) DALAM PERSPEKTIF AKADEMIK - simon nahak (Jurnal Hukum Prasada, 2017)
Abstract Philosophical foundation created law is to protect human dignity, and then fit the philosophical grounding one of the functions of the criminal law is as a means to control and reduce the occurrence of the crime of using criminal sanctions. Of the various types of sanctions it appears that administrative sanctions and civil penalties is less effective to instill a deterrent for the perpetrators. Therefore the use of criminal sanctions is still the best means available to deal with crime, especially for crime prevention Cyber Crime. Cyber Crime crime prevention in criminal theory should pay attention to three (3) concepts namely, act, guilt and punishment, while in practice criminal system through the Criminal Justice System, the author describes 5 (five) concept in the face of the criminal case; actors, documentary evidence / witnesses, penal mediation of peace between the perpetrator to the victim either at the level of police, prosecutors and courts to justify the consideration of the demands of the public prosecutor, Advocate Actors plea and verdict the judges to alleviate even liberate the perpetrators ". Keywords : Penal,Cyber Crime, Academic